2014
DOI: 10.1016/j.bbadis.2014.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Early alterations in energy metabolism in the hippocampus of APPswe/PS1dE9 mouse model of Alzheimer's disease

Abstract: The present study had focused on the behavioral phenotype and gene expression profile of molecules related to insulin receptor signaling in the hippocampus of 3 and 6 month-old APPswe/PS1dE9 (APP/PS1) transgenic mouse model of Alzheimer's disease (AD). Elevated levels of the insoluble Aβ (1-42) were detected in the brain extracts of the transgenic animals as early as 3 months of age, prior to the Aβ plaque formation (pre-plaque stage). By the early plaque stage (6 months) both the soluble and insoluble Aβ (1-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
100
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(117 citation statements)
references
References 72 publications
15
100
1
1
Order By: Relevance
“…In contrast, in Experiment 1 mice of the same age were not significantly impaired on a relative recency task, supposedly a measure of self-generated priming [52]. In both experiments the transgenic mice performed normally on the SOR task, mirroring previous work using animals of this age [40,42]. These results, although preliminary, are consistent with the suggestion that the mice suffer a selective deficit in retrieval-but not self-generated priming at 5 months of age, and that it is only at 6 months of age that the selfgenerated priming condition is also affected, and hence a net impairment in SOR observed.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In contrast, in Experiment 1 mice of the same age were not significantly impaired on a relative recency task, supposedly a measure of self-generated priming [52]. In both experiments the transgenic mice performed normally on the SOR task, mirroring previous work using animals of this age [40,42]. These results, although preliminary, are consistent with the suggestion that the mice suffer a selective deficit in retrieval-but not self-generated priming at 5 months of age, and that it is only at 6 months of age that the selfgenerated priming condition is also affected, and hence a net impairment in SOR observed.…”
Section: Discussionsupporting
confidence: 64%
“…This widely-used task has revealed deficits in a wide range of different 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 transgenic models of AD [32], and impairments are routinely observed in older APPswe/PS1dE9 mice [33,34,35,36,37; but see 38]. SOR deficits are also occasionally reported in these mice at 6-7 months of age [34,39,40,41], but never in animals younger than 6 months [40,42]. As elevated levels of Aβ are present from around 3.5 months of age in this strain [6,7], it is difficult to explain the SOR deficits in terms of this factor.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to AD, in VaD, human brain neurotransmitter alterations are mild, e.g., for choline acetyltransferase activity, muscarinic receptor density, serotonin, dopamine, homovanillic acid, dopamine D1-and D2-receptor density, noradrenaline, and gamma aminobutyric acid (GABA), while 5-hydroxyindoleacetic acid (5-HIAA) shows a more pronounced deficiency. This data summarized here agree in principle with more recent conclusions of post-mortem human brain studies and experimental models (Ohara et al 1994;Pimlott et al 2004;Jia et al 2004;Tohgi et al 1996;Chen et al 2013;Lee et al 2014;Niwa et al 2002;Pedrós et al 2014;Knezovic et al 2015;Barilar et al 2015). CSF concentrations of choline were significantly higher in VaD patients compared to AD and controls but did no correlate with mini-mental state examination (MMSE) scores (Jia et al 2004;Tohgi et al 1996).…”
Section: Pathologysupporting
confidence: 92%
“…The deposition of aβ in mice could be used as an animal model for the study of AD because it is a well-characterized model (Choi et al 2014), (Pedrós et al 2014). In fact, several studies have shown that AD is induced by injections of aβ (25-35) We believe that the time interval of aβ injection in our research was not enough to cause changes, and consequently it was not possible to see the change in CK, AK and PK activities.…”
Section: Discussionmentioning
confidence: 99%